Hypotonia and intellectual disability without dysmorphic features in a patient with PIGN-related disease - Isabelle Thiffault; Britton Zuccarelli; Holly Welsh; Xuan Yuan; Emily Farrow; Lee Zellmer; Neil Miller; Sarah Soden; Ahmed Abdelmoity; Robert A. Brodsky; Carol Saunders (BMC, 2017)
Abstract Background Defects in the human glycosylphosphatidylinositol anchor biosynthetic pathway are associated with inherited glycosylphosphatidylinositol (GPI)-deficiencies characterized by a broad range of clinical phenotypes including multiple congenital anomalies, dysmorphic faces, developmental delay, hypotonia, and epilepsy. Biallelic variants in PIGN, encoding phosphatidylinositol-glycan biosynthesis class N have been recently associated with multiple congenital anomalies hypotonia seizure syndrome. Case presentation Our patient is a 2 year old male with hypotonia, global developmental delay, and focal epilepsy. Trio whole-exome sequencing revealed heterozygous variants in PIGN, c.181G > T (p.Glu61*) and c.284G > A (p.Arg95Gln). Analysis of FLAER and anti-CD59 by flow-cytometry demonstrated a shift in this patient's granulocytes, confirming a glycosylphosphatidylinositol-biosynthesis defect, consistent with PIGN-related disease. Conclusions To date, a total of 18 patients have been reported, all but 2 of whom have congenital anomalies and/or obvious dysmorphic features. Our patient has no significant dysmorphic features or multiple congenital anomalies, which is consistent with recent reports linking non-truncating variants with a milder phenotype, highlighting the importance of functional studies in interpreting sequence variants.